2010
DOI: 10.1038/aps.2010.152
|View full text |Cite
|
Sign up to set email alerts
|

Isochaihulactone protects PC12 cell against H2O2 induced oxidative stress and exerts the potent anti-aging effects in D-galactose aging mouse model

Abstract: Aim: To investigate the effect of isochaihulactone (also known as K8), a lignan compound of Bupleurum scorzonerifolium, on H 2 O 2 -induced cytotoxicity in neuronally differentiated PC12 cells (nPC12). Methods: Viability of neuronal PC12 cells was measured using MTT assay. Protein expression was determined by Western blot. Apoptotic cells was determined using TUNEL assay. D-galactose aging mice were used as a model system to study the anti-oxidant effects of isochaihulactone in vivo. Results: Pretreatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Similar changes of normal aging animals have been reported by Yu et al ) 35 ). Liu et al have reported that reproductive aging has been implicated by OS ( 36 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar changes of normal aging animals have been reported by Yu et al ) 35 ). Liu et al have reported that reproductive aging has been implicated by OS ( 36 ).…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al have reported that reproductive aging has been implicated by OS ( 36 ). Somatic aging in general, is involved in reproductive aging due to OS ( 35 ). OS causes damage to oocyte and embryos.…”
Section: Discussionmentioning
confidence: 99%
“…-galactose (D-gal), a physiological nutrient derived from lactose in milk, 1 is metabolized in animals by D-galactokinase and galactose-1-phosphate uridyltransferase (GALT). Although some researchers have challenged the D-gal-induced aging model, 2,3 some other researchers indicate that D-gal-treated animals showed some hallmarks of aging, such as a shortened lifespan, 4 cognitive dysfunction, 5 presbycusis, 6 increased oxidative stress, 4,7 decreased antioxidant enzyme activity, 8 diminished immune responses, 9 increased advanced glycation endproducts, 10 accumulation of mitochondrial DNA mutations, 11 and mitochondrial dysfunction.…”
Section: Introduction Dmentioning
confidence: 99%
“…The effect of Glupep on Aβ42–Cu 2+ -induced ROS generation was studied using the DCFDA assay in PC12 cells. 59 DCFDA (2,7-dichlorofluorescein diacetate) is a nonfluorescent compound utilized to quantify ROS strains such as hydroxyl, peroxyl, and other ROS species. DCFDA reacts with the ROS molecules formed from the Aβ42–Cu 2+ -mediated redox cycle and gets oxidized to fluorescent 2,7-dichlorofluorescein (DCF, λ ex = 495 nm and λ em = 529 nm).…”
Section: Resultsmentioning
confidence: 99%